(Inter)nationalising the antibiotic research and development pipeline. Issue 2 (February 2020) - Singer, Andrew C; Kirchhelle, Claas; Roberts, Adam P
Summary: In this Personal View, we critically examine the wider context of international efforts to stimulate commercial antibiotic research and development via public–private initiatives. Despite these efforts, antibiotics remain a global resource without an international support structure that is commensurate to the risks from antibiotic-resistant infections and the long-term nature of required solutions. To protect this resource, we propose a two-pronged antibiotic research and development strategy based on a short-term strengthening of incentives (such as market entry rewards) to maximise the delivery of existing opportunities in the pipeline, and on a concurrent medium-term to long-term establishment of a global, publicly funded antibiotic research and development institute. Designed sustainably to deliver novel and first-in-class antibiotics targeting key human health gaps, the institute and its staff would become a global resource that, unlike the private pharmaceutical sector, would be managed as an open science platform. Our model of internationalised public research and development would maximise scientific synergy and cross-fertilisation, minimise replication of effort, acquire and preserve existing know-how, and ensure equitable and sustainable access to novel and effective antibiotics. Its genuinely global focus would also help counteract tendencies to equate donor with global health priorities. Our proposal is not radical. Historical precedent and developments in other research areas show that sustained international funding of publicly owned research can hasten the delivery of critically needed drugs and lower barriers to access.